A novel method of emittance matching to increase beam transmission for cyclotron-based proton therapy facilities: simulation study. Issue 1 (1st January 2023) - Maradia, Vivek; Meer, David; Weber, Damian C; Lomax, Antony J; Schippers, Jacobus M; Psoroulas, Serena
Abstract: In proton therapy, high dose rates can reduce treatment delivery times, allowing for efficient mitigation of tumor motion and increased patient throughput. With cyclotrons however, high dose rates are difficult to achieve for low-energies as, typically, the emittance after the degrader is matched in both transversal planes using circular collimators, which does not provide an optimal matching to the acceptance of the following beamline. Transmission can however be substantially improved by transporting maximum acceptable emittances in both orthogonal planes, but at the cost of gantry angle-dependent beam shapes at isocenter. Here we demonstrate that equal emittances in both planes can be recovered at the gantry entrance using a thin scattering foil, thus ensuring gantry angle-independent beam shapes at the isocenter. We demonstrate in simulation that low-energy beam transmission can be increased by a factor of 3 using this approach compared to the currently used beam optics, whilst gantry angle-independent beam shapes are preserved. We expect that this universal approach could also bring a similar transmission improvement in other cyclotron-based proton therapy facilities.